Method for Analysis and Study of Migration of Lead, Cadmium, Mercury and Arsenic from Polypropylene Packaging into Ice Cream and Simulant - Kiyataka, Paulo Henrique M.; et. al. (2015)
The aim of this study was to propose a method for analysis of lead (Pb), cadmium (Cd), mercury (Hg) and arsenic (As) in polypropylene packaging intended for contact with ice cream and migration of these elements using the food itself and 3 % acetic acid as food simulant. Ten commercial samples of ice cream marketed in Campinas-São Paulo (Brazil) were used for the analysis. Both the packaging and ice cream were digested in high-pressure ashing equipment (HPA), as a new proposal to the sample preparation and the migration of the elements into stimulant directly in the solution. The determinations were carried out using an inductively coupled plasma optical emission spectroscopy (ICP-OES) and two different nebulizers (cross flow and Miramist, when necessary). The results obtained showed that the levels of Hg and As of all packaging were below the limit of quantification (LOQ) corresponding to 1.0 and 1.7 μg L−1, respectively. The highest levels of Cd and Pb were 0.45 and 1.64 mg kg−1, respectively. The migration of these elements into the ice cream after 365 days of contact at −20 °C was below the LOQs for all the samples assessed. The results of specific migration into 3 % acetic acid simulant showed concentrations of Cd, Hg and As below 5, 5 and 10 μg kg−1, respectively. The method developed can be applied for the determination of inorganic elements in polypropylene, ice cream and acetic acid by ICP-OES.